(untitled) (Iraqi Journal of Medical Sciences, 2024)
Background: Rheumatoid arthritis (RA) is a chronic autoimmune inflammatory disease that is characterized by the presence of autoantibodies and joint inflammation, which consequently leads to articular cartilage damage. Due to the tumor necrosis factor-alpha (TNF-?) crucial role in the pathogenesis of RA, TNF-? inhibitors have revolutionized this disease treatment. Objective: To evaluate the influence of the single nucleotide polymorphism (SNP) of TNF-? on the response to etanercept in RA patients. Methods: The study comprised of 60 RA patients and 25 healthy individuals. The age range of the participants was between 20 and 69 years. DNA sequencing was carried out by using conventional polymerase chain reaction (PCR) and sequencing. The blood samples were taken from the RA patients at the baseline before the administration of anti TNF-? therapy. The level of TNF-? in the sera was measured using an enzyme-linked immunosorbent assay (ELISA). Results: The TNF-?-308 G/G genotype was the most prevalent in Iraqi RA patients (78%), while there was no significant difference of TNF-?-308 G/A between responders and non-responder group. TNF-? -308 G/G or G/A genotype have no influence on the response to etanercept. The results indicate that the level of TNF-? was significantly different (P